Pelatihan Penyusunan Laporan Keuangan Entitas Berorientasi Non-laba (ISAK 35) Untuk Yayasan Roudlotul Jannah - Ilmiddaviq, Muhammad Bahril; Ainiyah, Nur (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Financial statements are crucial in every entity, both profit-oriented and non-profit-oriented. Financial statements can trigger conflicts between agents and principals. In addition, reliable and good financial reports can prevent and minimize fraud. Raudhlatul Jannah Foundation held an increase in human resource capability as a form of organizational commitment in realizing an accountable, sustainable and transparent organization, so the foundation held this training. This kind of activity can certainly increase organizational value, organizational financial performance and the speed and accuracy of decision making. This training has a significant impact on the reliability of the Raudhlatul Jannah Foundation's reporting financial reports, although the achievement of results has not been maximized due to constraints on the background of human resource education and the intensity of the short training time.